Correlation of Science Process Skills with Students' Creativity in Learning of Creative Problem Solving Model with an Inquiry Approach on the Simple Harmonic Motion - Sumarli Sumarli; Haris Rosdianto; Buyung Buyung (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
This study aimed to determine the correlation of science process skills with students' creativity in learning of creative problem solving model with an inquiry approach on the simple harmonic motion. The study method that was used is a correlation study between science process skills with students' creativity. The sample was chosen by using the purposive sampling technique that total of 34 students in X MIA5 grade of the academic year 2016/2017 in one of the senior high schools in Semarang. The data collection was conducted by using a science process skills test and creativity test in essay form on the simple harmonic motion. Data were analyzed through correlation test by Pearson Product Moment technique and t-test. The results showed the value of r is 0.332 with low category and the value of tcount is 1.992 lower than ttable is 2.042 with a significance level of 5% and df is 32. This indicated that there was no significant correlation between science process skills with students’ creativity in learning of creative problem-solving model with an inquiry approach on the simple harmonic motion. This meant that students with high science process skills do not always show high creativity too in learning of creative problem-solving model with an inquiry approach on the simple harmonic motion.